Analysis of Factors Related to Stroke Occurrence at William Booth Hospital Semarang - Hadinata, Kwik Vida Arianti; Cahyati, Widya Hari; Wijayanti, Yuni (Universitas Negeri Semarang, 2025)
Stroke is a serious disease that occurs when blood flow to the brain is disrupted, either due to a blockage in the blood vessels (ischemic stroke) or a rupture of the blood vessels (hemorrhagic stroke). This condition can cause brain cell death in a short period of time and is at risk of causing permanent disability. This study aims to analyze the factors associated with the occurrence of stroke in hypertensive patients at RSU William Booth Semarang. This research is a quantitative study with a nested case-control design, using electronic medical record data from RSU William Booth Semarang in 2023. The variables in this study are age, gender, blood sugar levels, total cholesterol levels, triglyceride levels, HDL levels, LDL levels, uric acid levels, and a history of heart disease. The analysis used includes univariate analysis, bivariate analysis with chi-square test. The variables that are statistically significant are age (p=0.005), gender (p=0.021), random blood sugar levels (p=0.010), total cholesterol levels (p=0.009), triglyceride levels (p=0.034), HDL blood levels (p=0.049), LDL blood levels (p=0.034), and history of heart disease (p=0.023). The conclusion of this study is that early detection and management of risk factors, especially blood pressure control and cholesterol levels, are very important in preventing stroke. Educating the public about healthy lifestyles can also help reduce the incidence of strokes in the future.